1994
DOI: 10.1128/cmr.7.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of enterococci

Abstract: Enterococci are commensal organisms well suited to survival in intestinal and vaginal tracts and the oral cavity. However, as for most bacteria described as causing human disease, enterococci also possess properties that can be ascribed roles in pathogenesis. The natural ability of enterococci to readily acquire, accumulate, and share extrachromosomal elements encoding virulence traits or antibiotic resistance genes lends advantages to their survival under unusual environmental stresses and in part explains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
408
1
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(420 citation statements)
references
References 232 publications
(304 reference statements)
5
408
1
6
Order By: Relevance
“…Maki and Agger (1988) showed that nosocomial bacteraemias increased markedly between 1973 The virulence of enterococci has been reviewed by Jett et al (1994). A number of virulence factors have been implicated and 1983 against a constant 'back-drop' of community-acquired enterococcal bacteraemias.…”
Section: Pathogenesismentioning
confidence: 99%
“…Maki and Agger (1988) showed that nosocomial bacteraemias increased markedly between 1973 The virulence of enterococci has been reviewed by Jett et al (1994). A number of virulence factors have been implicated and 1983 against a constant 'back-drop' of community-acquired enterococcal bacteraemias.…”
Section: Pathogenesismentioning
confidence: 99%
“…virulence determinants of enterococci, which include a cytolysin, aggregation substance, pheromones, lipoteichoic acid, a protease, Enterococci are typically found in the intestinal tract and faeces of man and other animals (Murray 1990;Devriese and hyaluronidase and a bacteriocin, 45-48 (Jett et al 1994). As well as being well adapted for survival in the body, Pot 1995).…”
Section: Of Enterococcusmentioning
confidence: 99%
“…14) Like other enterococci, E. faecalis causes life-threatening nosocomial infections because of its high multidrug resistantce. [15][16][17] Additionally, the production of toxic or virulent factors, such as adhensin, hemolysin, and gelatinase, may be related to the pathogenicity of this species. [15][16][17] In particular, the gelatinase GelE has been studied as an important toxic factor involved in bacterial invasion.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Additionally, the production of toxic or virulent factors, such as adhensin, hemolysin, and gelatinase, may be related to the pathogenicity of this species. [15][16][17] In particular, the gelatinase GelE has been studied as an important toxic factor involved in bacterial invasion. 18,19) Additionally, this extracellular enzyme can digest many host proteins including fibrinogen, fibronectin, collagen, and laminin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation